Record based evaluation of national leprosy eradication programme in Jamnagar district - Yadav S (Wolters Kluwer Medknow Publications, 2007)
Background : With a view to eliminate leprosy, Government launched National Leprosy Eradication Programme in 1983. Modified Leprosy Elimination Campaigns further helped in case detection. Objective : To evaluate the impact of National Leprosy Eradication Programme in Jamnagar district. Methods : A retrospective record based study was conducted in Urban Leprosy Centre of Jamnagar district. Prevalence rate, New case detection rate, Percentage of cases released from treatment, Proportion of multibacillary (MB) cases among new cases, Proportion of grade II disability among new cases and Proportion of child cases among new cases were evaluated. Results: Analysis of records of ten years indicated a decrease in prevalence rate of leprosy. Over the years a declining trend in grade II disability among new cases was noted. There was an increase in percentage of patients being released from treatment. Case detection rate was increasing steadily from year 1992 to1998. Analysis of data relating to proportion of cases among children did not show a consistency in trend. Conclusion : The national leprosy eradication programme has a favorable impact towards elimination of leprosy in the district of Jamnagar.